1989
DOI: 10.1136/thx.44.10.826
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of tumour cells from fine needle biopsy.

Abstract: A 53 year old woman developed a cutan-ẽ ous tumour implant in the needle track after transcutaneous fine needle biopsy of a pulmonary adenocarcinoma. The tumour implant was completely excised.The value of fine needle biopsy in the diagnosis of discrete lung shadows seen on chest radiographs is firmly established."2 The procedure is not, however, entirely without immediate or long term risk. Case reportA nervous 53 year old housewife presented withjoint pains, a dry cough, and a chest radiograph showing a left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Despite high diagnostic accuracy and low short term complications have been widely studied for years, it is necessary to understand the long term comorbidities like pleural recurrence related to diagnostic procedure. Some typical cases with pleural recurrence and needle tract implantation have been identified since 1965 when PTNB was firstly reported to be used 4 5 21 22 23 . A cohort study, however, was lack until 2005 Matsuguma, et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite high diagnostic accuracy and low short term complications have been widely studied for years, it is necessary to understand the long term comorbidities like pleural recurrence related to diagnostic procedure. Some typical cases with pleural recurrence and needle tract implantation have been identified since 1965 when PTNB was firstly reported to be used 4 5 21 22 23 . A cohort study, however, was lack until 2005 Matsuguma, et al .…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous transthoracic needle biopsies (PTNB) are widely used for the histologic diagnosis of a peripheral indeterminate pulmonary nodule and reported a high diagnostic yield of 90% sensitivity and 97% specificity 1 2 . However, pleural recurrence was also reported as a long term complication of PTNB in many literatures 3 4 5 6 . Recent evidence focusing on recurrent outcomes after PTNB was controversial 7 8 9 10 11 .…”
mentioning
confidence: 99%
“…Seeding of malignant cells in the needle tract following PNB is also rare; only two cases were reported by Muller et al in a review of 5300 patients [61]. There have been other occasional reports of tumor cell dissemination [62][63][64][65][66][67][68][69], including a report of two cases in which there was cancer dissemination into the pleural space [70]. It has been suggested that the risk of tumor cell seeding must be strongly considered when deciding whether to biopsy potentially operable malignant lesions [71].…”
Section: Tumor Implantationmentioning
confidence: 99%
“…Iatragenic seeding has been reported in patients with hepatocellular carcinoma, bronchogenic carcinoma (5), prostate cancer (6), and brain cancer, as well as many other types of histopathologic malignancies following needle biopsy. The incidence of tumor seeding associated with needle biopsy increases progressively with larger needle diameters (2,3).…”
Section: Discussionmentioning
confidence: 99%